Ultrafast H2-selective nanoporous multilayer graphene membrane prepared by confined thermal annealing. Issue 70 (9th August 2021) - Kim, Jeong Pil; Choi, Eunji; Kang, Junhyeok; Choi, Seung Eun; Choi, Yunkyu; Kwon, Ohchan; Kim, Dae Woo
Abstract : Ultrafast and H2 -selective nanoporous graphene membrane was fabricated by thermally treating the GO layer in a confined space under high pressure. Abstract : H2 selective dense pores are generated in a graphene oxide (GO) layer by thermal-decomposition of oxygen-functional groups under high pressure. The nanoporous GO membrane shows H2 /CO2 selectivity of 12.1 and H2 permeability of 10360 Barrer.